(untitled) (Biological Sciences - PJSIR, 2006)
This study examines the allelopathic effect of different concentrations of aqueous extracts obtained from the decomposed leaves and soil beneath Chromoleana odorata (siam weed) and Euphorbia heterophyalla (wild poinsettia) on the elongation of radicle and plumule of cowpea. All the extracts were found to retard the elongation of both radicle and plumule when compared to the control. Statistical analyses at 5% level, however, revealed that the degree of retardation was not significantly different. Extracts from the decomposed leaves of C. odorata andheterophylla brought about considerable slowing down of the rates of radicle elongation in cowpea. Also, while the extracts derived from soil beneath C. odorata resulted in mere reduction in the elongation of cowpea plumule, those derived from soil beneath E. heterophylla resulted in delayed germination of the plumule in addition to slowing down the rate of elongation.